2019
DOI: 10.1088/1757-899x/577/1/012188
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of stainless steels in acidic, neutral and alkaline saline media: Electrochemical and microscopic analysis

Abstract: This study presents how SS304 and SS316 corrode in saline media, including in the presence of acid and alkali, through an electrochemical and microscopic analysis. SS304 and SS316 samples were studied for their corrosion resistance in 1M NaCl, and in the presence of either 1M HCl or 1M NaOH. Potentiodynamic polarization studies were carried out to determine the corrosion potentials and currents. From the anodic polarization, regions corresponding to corrosion, passivation and transpassivation were identified. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…6c). The drastic reduction in weight loss is not unusual because corrosion in acidic environments has been shown to be generally more severe than in alkaline media [30]. Unlike the activity of H + from the 0.5M HCl on the alloy elements, the aqueous NaOH (0.5M) species only interacts with a few of the alloy elements, i. e. Diffusion and the resultant trapping of the alloy elements as well as increase in the interatomic bond over the heat treatment process leading to the improved mechanical properties of the austempered AISI 1018 specimen from the microstructural transformation also lead to a consequential reduction in the tendency of both Zn and Al alloys the react with the NaOH species in the alkaline media.…”
Section: Corrosion In the Alkaline Mediummentioning
confidence: 99%
“…6c). The drastic reduction in weight loss is not unusual because corrosion in acidic environments has been shown to be generally more severe than in alkaline media [30]. Unlike the activity of H + from the 0.5M HCl on the alloy elements, the aqueous NaOH (0.5M) species only interacts with a few of the alloy elements, i. e. Diffusion and the resultant trapping of the alloy elements as well as increase in the interatomic bond over the heat treatment process leading to the improved mechanical properties of the austempered AISI 1018 specimen from the microstructural transformation also lead to a consequential reduction in the tendency of both Zn and Al alloys the react with the NaOH species in the alkaline media.…”
Section: Corrosion In the Alkaline Mediummentioning
confidence: 99%
“…Furthermore, we used an accelerated corrosion test using saline, acidic, and oxidising solution. To our knowledge, there are few examples of tests carried out in such corrosive solutions [40][41][42] on ALD-coated supports. The corrosion protection behaviour of the fabricated coatings was assessed by potentiodynamic polarisation tests in a simulated corrosive environment (0.9% NaCl + 6% H 2 O 2 , pH = 4).…”
Section: Introductionmentioning
confidence: 99%
“…Tungsten carbide (WC) or chromium carbide (Cr 3 C 2 ), or a combination of these materials, are the most commonly used carbide-based thermal spray coatings. [1][2][3][4][5] Some studies reported that WC-based coatings exhibited better erosion resistance to the steel and Ni-based substrate material. WC-Co-based coatings protected the steel substrates from wet and dry abrasion conditions and also observed that finer WC particles were associated with increased wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have performed substantial research into the elements that influence erosion, erosion mechanisms, and material erosion resistance to combat erosion. Tungsten carbide (WC) or chromium carbide (Cr 3 C 2 ), or a combination of these materials, are the most commonly used carbide‐based thermal spray coatings 1–5 . Some studies reported that WC‐based coatings exhibited better erosion resistance to the steel and Ni‐based substrate material.…”
Section: Introductionmentioning
confidence: 99%